Analisis Perhitungan Harga Pokok Produksi Dengan Metode Full Costing Dan Penentuan Harga Jual Dengan Pendekatan Cost Plus Pricing Sebagai Upaya Memperoleh Laba Optimal (Studi Kasus Pada Usaha Kripik Pisang Berkah Jaya Kelurahan Yosodadi, Metro Timur) - Sari, Erna; Nusantoro, Jawoto; Sari, Gustin Padwa (Expensive: Jurnal Akuntansi dan Keuangan, 2022)
The purposes of this study are (1), to determine the calculation of the cost of production using the full costing method and determining the selling price using the cost plus pricing approach (2), to determine the calculation of the cost of production and determining the selling price applied by business owners (3), to find out the comparison between the two calculations. The object of the research is the BERKAH JAYA Banana Chips Business, Yosodadi Village, East Metro. The types of data in this study are qualitative and quantitative data, while the data sources used in this study are primary and secondary data. Data collection techniques used are observation, interviews, and literature. The data analysis method is to identify costs, compile data, calculate the cost of goods using the full costing method and selling prices with the cost plus pricing approach, calculate the cost of production and the selling price of the business owner and then make a comparison. The results of this study indicate that the calculation of the cost of production and selling prices with the standard method is higher than the business owner's method, so that the full costing method and the cost plus pricing approach can be used as an effort to obtain optimal profit